2013
DOI: 10.3389/fnhum.2013.00487
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and socioemotional aging: Current knowledge and future trends

Abstract: The oxytocin (OT) system is involved in various aspects of social cognition and prosocial behavior. Specifically, OT has been examined in the context of social memory, emotion recognition, cooperation, trust, empathy, and bonding, and—though evidence is somewhat mixed-intranasal OT appears to benefit aspects of socioemotional functioning. However, most of the extant data on aging and OT is from animal research and human OT research has focused largely on young adults. As such, though we know that various socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 189 publications
(268 reference statements)
2
63
0
1
Order By: Relevance
“…A small number of studies have addressed the effects of OT in clinically depressed patients. It is necessary to better understand how oxytocin influences cognition since it seems to be mediated by different factors and contexts (Ebner et al, 2013). Further studies in clinically depressed patients or remitted patients are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of studies have addressed the effects of OT in clinically depressed patients. It is necessary to better understand how oxytocin influences cognition since it seems to be mediated by different factors and contexts (Ebner et al, 2013). Further studies in clinically depressed patients or remitted patients are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The OTR and OT are involved in memory and learning, stress regulation and anxiety, and aggressive, sexual and maternal behaviors (e.g. Argiolas 1992, Malik et al 2012, Ebner et al 2013. Moreover, the OTR is involved in thermoregulation and brain development (Gimpl & Fahrenholz 2001, Kasahara et al 2013).…”
Section: R68 Reviewmentioning
confidence: 99%
“…None of these effects were present in younger adults. Ebner et al (2013) investigated the association of the oxytocin receptor (OXTR, rs237887) polymorphism, previously associated with susceptibility to prosocial behavior, to face recognition and BOLD activity in younger and older adults. Results showed that OXTR modulated activity in anterior cingulate cortex of older adults only.…”
Section: Miscellaneous Genesmentioning
confidence: 99%